2001
DOI: 10.1007/s002800100300
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase as a new target for cancer chemotherapy

Abstract: Trichostatin A (TSA) and trapoxin (TPX), inhibitors of the eukaryotic cell cycle and inducers of morphological reversion of transformed cells, inhibit histone deacetylase (HDAC) at nanomolar concentrations. Recently, FK228 (also known as FR901228 and depsipeptide) and MS-275. antitumor agents structurally unrelated to TSA, have been shown to be potent HDAC inhibitors. These inhibitors activate the expression of p21Waf1 in a p53-independent manner. Changes in the expression of regulators of the cell cycle, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
147
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(152 citation statements)
references
References 0 publications
3
147
0
2
Order By: Relevance
“…This would be much easier than using immunoprecipitated subtypes and a nonselective substrate. We compared the subtype selectivities of two TSA-like inhibitors 17 M344 (16b) and M360 (16c) and three structurally unrelated cyclotetrapeptide inhibitors (CHAPs 18,19 ) ( Figure 4). M344 (16b) was selective for HDAC6 vs HDAC1 (IC 50 , 88 vs 249 nM).…”
Section: Synthesismentioning
confidence: 99%
“…This would be much easier than using immunoprecipitated subtypes and a nonselective substrate. We compared the subtype selectivities of two TSA-like inhibitors 17 M344 (16b) and M360 (16c) and three structurally unrelated cyclotetrapeptide inhibitors (CHAPs 18,19 ) ( Figure 4). M344 (16b) was selective for HDAC6 vs HDAC1 (IC 50 , 88 vs 249 nM).…”
Section: Synthesismentioning
confidence: 99%
“…Acetylation neutralizes the charge of the histones and generates a more open DNA conformation. Since aberrant histone acetylation has been linked to malignant diseases in some cases, HDAC inhibitors (HDIs) have potential as new drugs due to their ability to modulate transcription and to induce differentiation and apoptosis (5). Molecular analyses of human diseases have suggested that changes in acetylation may play a role in the uncontrolled cell growth of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] HDACIs also induce cell cycle arrest at the G 1 and/or G 2 /M phases of the cell cycle, cause differentiation and/or apoptosis, and exhibit potent anti-tumor activity against a variety of tumor cells, both in vitro and in vivo. [1][2][3][4][5][6][7][8] In addition, HDACIs have the advantage of being less toxic in normal cells than in cancer cells. [10][11][12][13][14] Based on their pleiotropic cellular effects and their tumor-selectivity, several HDACIs are currently undergoing clinical trials, and some of them have shown promising anti-tumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Modulating gene expression by using HDACIs may therefore represent a significantly more powerful approach to treat cancer than the targeting of a single genetic pathway. [3][4][5][6][7][8] HDACIs treatments have been shown to cause hyperacetylation of nucleosomal histones of condensed chromatin, and thus, to effect the reactivation of silenced genes. [3][4][5][6][7][8][9] HDACIs also induce cell cycle arrest at the G 1 and/or G 2 /M phases of the cell cycle, cause differentiation and/or apoptosis, and exhibit potent anti-tumor activity against a variety of tumor cells, both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation